The crystal structure of oxonium hexaquaaluminium disulfate hexahydrate - Liu Yan; Hao Min; Gao Jianfeng; Liu Jianghui; Cui Juan (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
AlH27S2O21, cubic, Pa3̄ (no. 205), a = 12.2403(14) Å, V = 1833.9(6) Å3, Z = 4, Rgt(F) = 0.0507, wRref(F2) = 0.1458, T = 298 K.